Pola makan terhadap kejadian obesitas pada remaja: Tinjauan Literature - Siti Fainurryzky Annisa (DAPU Aceh Publishing, 2025)
The obesity is a condition that occurs in the body fat stockpiled more than typical fat, this is because energy intake with energy expended there is an imbalance. When in adolescence someone is obese, they will be at risk of suffering from obesity and comorbidities in adulthood and even the elderly. This literature review aims to summarize and discuss topics regarding diet on nutritional problems in adolescents, namely the incidence of obesity using previous research. The research method uses literature review / literature review. The data in this study were sourced from the internet in the form of articles obtained through literature studies and research results on dietary patterns on obesity through “Google Scholar”, “BMC Public Health”, and “Pubmed”, the last 10 years 2019-2024. The results of this literature review from 10 journals that have been reviewed, the conclusion of this study is that it is clearly proven significantly that diet is related to the incidence of obesity in adolescents. Therefore, the author hopes that this literature review can increase readers' knowledge about diet on the incidence of obesity experienced by adolescents